APRESENTAÇÃO - Canavarro Benite, Anna M.; Camargo Vianna, Cintia; Otaviana Barbosa de Sá Figueiredo, Mércia; Novaes da Silva, José Antonio (Revista da Associação Brasileira de Pesquisadores/as Negros/as (ABPN), 2020)
PRÉSENTATION